July jitters - Roy, Ron, 1940- (Calendar mysteries, 2012)
Bradley, Brian, Nate, and Lucy enter Polly the pony and Pal the dog in a July 4th pet costume contest, but when Independence Day arrives the animals are nowhere to be found.